2014
DOI: 10.3340/jkns.2014.56.6.496
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Sundt Clip Graft in a Previously Coiled Internal Carotid Artery Blister-Like Aneurysm

Abstract: Owing to the focal wall defect covered with thin fibrous tissues, an aneurysm arising from the dorsal wall of the internal carotid artery (ICA) is difficult to manage either surgically or endovascularly and is often associated with high morbidity and mortality. Unfortunately, the definitive treatment modality of such highly risky aneurysm has not yet been demonstrated. Upon encountering the complex intracranial pathophysiology of such a highly precarious aneurysm, a neurosurgeon would be faced with a challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Intracranial fusiform aneurysms are rare, although the number of cases has increased in recent years, mainly in young patients. [413162029] They represent about 3–13% of all intracranial aneurysms and they are often presented at the vertebrobasilar system. [2024] Fusiform aneurysms in the anterior circulation are less frequent when compared with the posterior circulation and most of the times, the middle cerebral artery (MCA) is the most affected, followed by the internal carotid artery (ICA) and the anterior cerebral artery (ACA).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intracranial fusiform aneurysms are rare, although the number of cases has increased in recent years, mainly in young patients. [413162029] They represent about 3–13% of all intracranial aneurysms and they are often presented at the vertebrobasilar system. [2024] Fusiform aneurysms in the anterior circulation are less frequent when compared with the posterior circulation and most of the times, the middle cerebral artery (MCA) is the most affected, followed by the internal carotid artery (ICA) and the anterior cerebral artery (ACA).…”
Section: Introductionmentioning
confidence: 99%
“…The patient can present symptoms and signs of occlusion, arterial rupture, or mass effect. [42024] Fusiform aneurysms present more often with ischemic stroke or mass effect. [27]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cho et al 2) and Cho et al 3) reported separately the modified application of Sundt clip, which was placed over the stented or stent-associated coiled artery before Sundt clip operation. Besides, in case 5 and 20, there showed the other possibility of reinforcement of Sundt clip by Yasargil clip or bam sheet.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of dorsal wall aneurysm have been challenged by many neurosurgeons with various modalities (conventional clip, clip with wrapping, using Sundt [encircling] clip, trapping, and stent assisted coil, etc). 2) 5) 7) 9) 10) 11) 16) 17) 18) Although the advancement in microneurosurgery and endovascular techniques have been archived, the optimal treatment of BBA remained controversy. The dorsal wall aneurysm comprise 0.9–6.5% of all ICA aneurysm, 12) furthermore BBA comprise much smaller percentage of all ICA aneurysm.…”
Section: Introductionmentioning
confidence: 99%